The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ctcp.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Secondary psychological outcomes in a controlled trial of Emotional Freedom Techniques and cognitive behaviour therapy in the treatment of food cravings

Abstract: The current study supports the hypothesis that psychological intervention is beneficial for treating psychological comorbidities of obesity and points to the role mental health issues may play in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
(34 reference statements)
1
22
0
Order By: Relevance
“…While speculatively, the neural changes indicated in this pilot study appear to compare to the self-reported food craving decreases in the current trial as well as previous EFT and food craving trials [19][20][21][22]. The lack of engagement in homework activities reported by participants (addressed next) and the relative deactivation of the brain activity during the post scans while viewing high caloric food images, suggests a correlation worth examining in larger future trials.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…While speculatively, the neural changes indicated in this pilot study appear to compare to the self-reported food craving decreases in the current trial as well as previous EFT and food craving trials [19][20][21][22]. The lack of engagement in homework activities reported by participants (addressed next) and the relative deactivation of the brain activity during the post scans while viewing high caloric food images, suggests a correlation worth examining in larger future trials.…”
Section: Discussionmentioning
confidence: 49%
“…Finally and worthy of note is that while the EFT participants were encouraged to engage in the technique outside sessions, and reminder messages were sent by the lead therapist between sessions every week. However, they typically did not do so via self-report and this was also indicated in previous trials [19][20][21][22]. A recent two year follow-up of an 8-week online intervention program for overweight or obese adults found participants' food craving, perceived power of food, dietary restraint capabilities and all psychological distress symptoms (i.e.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, the low magnitude of the differences at the emotional level together with the modest efficacy in maintaining long-term weight loss (Cooper et al, 2010) and binge eating reduction (Juarascio et al, 2017;Palavras et al, 2017), indicate the need for improved interventions. In acknowledgment of the importance of emotions in obesity, new CBT programs have put greater emphasis on emotion regulation training, such as impulsive eating (Preuss et al, 2017), food cravings (Stapleton et al, 2017), emotional functioning (Buckroyd et al, 2006;Buckroyd and Rother, 2007), and emotion regulation skills (Pjanic et al, 2017). In general, these new CBT programs found encouraging results in terms of emotional functioning (Buckroyd et al, 2006;Pjanic et al, 2017;Stapleton et al, 2017), eating behavior (Preuss et al, 2017;Stapleton et al, 2017) and weight loss (Buckroyd et al, 2006;Preuss et al, 2017).…”
Section: Introductionmentioning
confidence: 99%